PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL DAN METODE DISKUSI TERHADAP HASIL BELAJAR SISWA SMP - Didit Darmawan; Putri, Daffa Nayla Oktavia Hermawan; Muhammad Zajuli Yusuf (widya balina, 2026)
The use of digital learning media and discussion methods is increasingly important to support junior high school students' learning outcomes. Digital media, such as videos, animations, and interactive platforms, facilitate understanding of material and increase learning motivation, while discussion methods encourage active participation, critical thinking, and student reflection. This study examines the influence of the use of digital learning media and discussion methods on junior high school students to obtain a comprehensive picture of the effectiveness of both variables in improving student learning outcomes. A qualitative method with a literature review approach was used as the research method. Sources were obtained from relevant journals, articles, and books, and analyzed descriptively and qualitatively. The results found that the use of digital media and discussion methods had a positive effect on student learning outcomes. Implications emphasize the importance of adequate technological facilities and teacher training to utilize digital media and discussion methods to create enjoyable and interactive learning.